Abundance of springtails (Collembola) under four agroforestry tree species with contrasting litter quality - Badejo, M.A.; Nathaniel, T.I.; Tian, G. (1998)
The soil- and litter-dwelling Collembola under four agroforestry tree species (Treculia ajricana, Dactylaaenia (Acioa) barteri, Gliricidia sepium and Leucaena leu'cocephala) were monitored monthly for a period of 12 months and results were compared with those of a secondary forest and a grass plot. Treculia and Dactyladenia produced lower quality litter, leading to lower soil temperature and higher soil moisture under those species, relative to Gliricidia and Leucaena. The agroforestry tree plots contained more soil- and litter-dwelling Collembola than the secondary forest and grass plots. The slowly decomposing litter under Treculia and Dactyladenia supported more litter Collembola than the quickly decomposing litter under Gliricidia and Leucaena. Soil moisture and temperature were, respectively, positively and negatively correlated with populations of soil Collembola. Based on the results of this study, it is suggested that the use of prunings of agroforestry tree species as mulch in agroecosystems would encourage the growth of Collembola populations and enhance their role in decomposition processes.